2012
DOI: 10.1177/1066896912464047
|View full text |Cite
|
Sign up to set email alerts
|

Composite Peripheral T-cell Lymphoma Not Otherwise Specified, and B-cell Small Lymphocytic Lymphoma Presenting With Hemophagocytic Lymphohistiocytosis

Abstract: We report a case of a 68-year-old female patient who developed hemophagocytic lymphohistiocytosis (HLH) secondary to peripheral T-cell lymphoma (PTCL) not otherwise specified (NOS) that developed in the setting of treatment-resistant B-cell small lymphocytic lymphoma/chronic lymphocytic leukemia (SLL/CLL). The patient's B-cell lymphoma had a good initial response to chemotherapy for 4 years, after which it became less responsive and was thought to have undergone transition to a higher-grade lymphoma. Different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
0
18
1
Order By: Relevance
“…In contrast to most of the PTCLs previously encountered, 2 of our 3 patients had ALK + ALCL, both occurring in women. 19 The clinical features of our 3 cases and of other cases of PTCL in CLL patients 6,18,[20][21][22][23][24][25][26][27][28][29][30] are summarized in Tables 1 and 3. One additional case of ALK + ALCL arising in a patient with CLL/SLL has been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to most of the PTCLs previously encountered, 2 of our 3 patients had ALK + ALCL, both occurring in women. 19 The clinical features of our 3 cases and of other cases of PTCL in CLL patients 6,18,[20][21][22][23][24][25][26][27][28][29][30] are summarized in Tables 1 and 3. One additional case of ALK + ALCL arising in a patient with CLL/SLL has been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the reported CLL/SLL patients who developed PTCLs had received prior therapy for CLL, 6,19,21,24,[26][27][28] raising the possibility that the T-cell lymphomas may arise because of the immunosuppression associated with prior therapy, superimposed on the immunodeficiency inherent to CLL and the complex interplay between the CLL and nonneoplastic T cells. The majority of the reported CLL/SLL patients who developed PTCLs had received prior therapy for CLL, 6,19,21,24,[26][27][28] raising the possibility that the T-cell lymphomas may arise because of the immunosuppression associated with prior therapy, superimposed on the immunodeficiency inherent to CLL and the complex interplay between the CLL and nonneoplastic T cells.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,[12][13][14] Although we did not attempt to demonstrate clonal rearrangement of a T-cell receptor genetic locus, neither T-cell receptor rearrangement is universally present in C-ALCL nor is it required for the diagnosis. [27][28][29] In conclusion, this report describes a rare case of CL involving MCL and C-ALCL in the skin of an elderly man. PAX5 is an extremely sensitive and specific marker of B lymphoid differentiation in human neoplasms; its complete absence in the C-ALCL component in our case argues strongly against a B lineage lymphoma, such as MCL or classical HL.…”
Section: Discussionmentioning
confidence: 71%
“…Many had identified or suspected an infectious trigger, such as histoplasma,6 EBV,12 influenza A13 or atypical mycobacterium 14. Underlying T-cell lymphomas were found in patients with B-CLL and HLH 15. Other case reports implicate fludarabine or rituximab in the development of HLH in CLL;16 however, a case report by Meki et al 17 concluded that HLH was present in an early stage prior to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%